1985
DOI: 10.1063/1.95679
|View full text |Cite
|
Sign up to set email alerts
|

Low pressure chemical vapor deposition of titanium silicide

Abstract: The low pressure chemical vapor deposition (LPCVD) of titanium silicide is reported here for the first time. X-ray diffraction spectra show that the as-deposited films are polycrystalline and TiSi2 is the predominant phase. The as-deposited films had resistivities of 22 to 39 μΩ cm with film thicknesses ranging from 2000 to 15 500 Å, and Si/Ti ratios of 1.8 to 2.3 as determined by Rutherford backscattering spectroscopy. Auger analyses did not detect any impurities such as oxygen and carbon in these films. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The increase of the polysilicon consumption rate with increasing TIC14 flow rate re- quires a close examination of the primary reactions responsible for the consumption of the polysilicon. These reactions are listed below TiCh* + 3Si(s) --~ TiSi2(s) + SiC12(g) [2] TiCI~* + 4Si(s) + 3H2" --> TiSi2(s) + 2SiC1Ha(g) [3] TIC14* + 3Si(s) --> TiSi2(s) + SiC14(g) [4] Si(s) + 3HCI* ---> SiC13H(g) + H2(g) [5] Si(s) + 3HCI* --~ SiC13(g) + 3/2 H2(g) [6] Si(s) + 2HCl* ~ SiC12H2(g) [7] where * denotes adsorption on a surface site and TIC12* and HCI* are generated by intermediate reactions. Increasing the flow of TIC14 from 2 to 4 sccm increases the TIC14 flux to the surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of the polysilicon consumption rate with increasing TIC14 flow rate re- quires a close examination of the primary reactions responsible for the consumption of the polysilicon. These reactions are listed below TiCh* + 3Si(s) --~ TiSi2(s) + SiC12(g) [2] TiCI~* + 4Si(s) + 3H2" --> TiSi2(s) + 2SiC1Ha(g) [3] TIC14* + 3Si(s) --> TiSi2(s) + SiC14(g) [4] Si(s) + 3HCI* ---> SiC13H(g) + H2(g) [5] Si(s) + 3HCI* --~ SiC13(g) + 3/2 H2(g) [6] Si(s) + 2HCl* ~ SiC12H2(g) [7] where * denotes adsorption on a surface site and TIC12* and HCI* are generated by intermediate reactions. Increasing the flow of TIC14 from 2 to 4 sccm increases the TIC14 flux to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…CVD of titanium silicide.--The reported work on the CVD of titanium silicide includes: atmospheric pressure CVD (APCVD) (4,5), low pressure CVD (LPCVD) (4,6), plasma enhanced CVD (PECVD) (4,7), and laser-induced CVD (LICVD) (8). Kemper et al (4) reported that the APCVD of titanium silicide in a temperature range of 800 ~ 1000~ and TiC14/SiH2CI~ ratios of 1.5-4 resulted in rough films with poor adhesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4"~''J'~''~-:6 Titanium disilicide is formed in a reaction between titanium tetraehloride and elemental silicon, where both hydrogen as well as silicon itself can act as reducing agents. Consider the reaction with no hydrogen present TiC14(g) + (2 + x)Si(s) --~ TiSi2(s ) + xSiC14,~(g) [7] One part of the silicon consumed in the reaction forms the silicide. The other part is oxidized to volatile silicon chlorides in an etching process.…”
Section: Selectivity--inmentioning
confidence: 99%
“…It has also been suggested that C49-C54 conversion occurs more readily for this process although this area still lacks an in-depth investigation. The CVD process was first introduced by Tedrow et al 7 in 1985, and it has attracted considerable interest from researchers in U.S., Japan, and France. [8][9][10][11][12][13][14][15][16] Silicides are formed on heavily doped source/drain regions and polycrystalline silicon gates.…”
mentioning
confidence: 99%